Credit Money as an Extraordinary Source of the "Militaristic Economy" and a Factor of World Economic Instability (1914-1945): Analysis of Money Theories in Russia - I.А.Nazarova; D.N. Platonov (Communications of International Proceedings, 2021)
The article shows that the development of money theory occurs under the influence of large-scale changes in the socio-economic system of industrially developed countries in the process of the formation of large monopolistic associations and the expansion of the market of imperfect competition. The change in economic technological structures leads, in the course of an extraordinary regrouping of political forces on the economic map of the world, to major changes in the monetary system in a number of countries. The article analyzes the role of credit money in the works of leading figures of the Russian economic theory of the first half of the 20th century during the period of intensive search for the most mobile budgetary resources to fund the needs of the "military economy". The conditions for the transition to monetary circulation associated with the violation of the multilateral clearing system, gold demonetization, factors of refusal to use traditional instruments of external debt repayment in the formation of the practice of bilateral clearing are considered. The role of money in the world as a factor accelerating the development of new markets and transmitting signals of economic instability in Russian literature of the 20th century is investigated. The conditions of ineffectiveness of the creation of special funds and the introduction of new taxes in emergency situations, when the use of the most mobile financial resources is required, are clarified. It is concluded that the dynamics of the accumulation of gold and foreign exchange reserves shows the specific role of gold in the formation of a new monetary and financial map of the world in the second half of the 20thcentury.
Keywords: Gold Demonetization; Credit Money; Extraordinary Budget; Multilateral Clearing; Bilaterism; "Gold Inflation"; Economic Thought.